2004
DOI: 10.1590/s0101-31222004000200002
|View full text |Cite
|
Sign up to set email alerts
|

Armazenamento de sementes de aveia preta produzidas em solos de diferentes fertilidades

Abstract: O trabalho objetivou estudar o comportamento de sementes de aveia preta (Avena strigosa Schreber) cv. Comum, produzidas em três condições distintas de fertilidade de solo e armazenadas em quatro ambientes diferentes. Os lotes foram armazenados por 60 meses, acondicionados em sacos de papel unifoliado, nas condições de ambiente natural de laboratório, de câmara seca (30 a 40% de U.R.), de geladeira ( 5 a 7ºC) e de "freezer" (-20ºC). As avaliações do teor de água e da germinação foram realizadas em intervalos tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
1
5
1
1
Order By: Relevance
“…Ullmann et al (2018) and Zucareli et al (2015) in studies on sorghum and carioca common bean, respectively, observed that seeds of these species stored with a higher moisture content deteriorate more rapidly, suggesting that moisture content is a factor that may considerably affect seed longevity. In contrast, in the present study, the seed moisture content in each environment over the storage period showed small changes, therefore indicating that the moisture content may not have been the most influential factor in maintaining the physiological quality of the seeds (Nakagawa et al, 2004).…”
Section: Resultscontrasting
confidence: 95%
See 2 more Smart Citations
“…Ullmann et al (2018) and Zucareli et al (2015) in studies on sorghum and carioca common bean, respectively, observed that seeds of these species stored with a higher moisture content deteriorate more rapidly, suggesting that moisture content is a factor that may considerably affect seed longevity. In contrast, in the present study, the seed moisture content in each environment over the storage period showed small changes, therefore indicating that the moisture content may not have been the most influential factor in maintaining the physiological quality of the seeds (Nakagawa et al, 2004).…”
Section: Resultscontrasting
confidence: 95%
“…These results corroborate those obtained for sudangrass (Sorghum sudanense) seeds, in which the refrigerator and freezer environments, followed by the dry chamber, led to more adequate conservation than the natural laboratory environment, which had faster loss of vigor (Toledo et al, 2007;Toledo et al, 2013). In black oat seeds, the refrigerator and freezer environments were also more favorable for conservation than the dry chamber environment and natural environment (Nakagawa et al, 2004).…”
Section: Dry Chambersupporting
confidence: 85%
See 1 more Smart Citation
“…Verificou-se, também, que as sementes de sorgo-sudão apresentaram melhor conservação sob condições de baixa temperatura e umidade relativa. Os resultados corroboram com os obtidos por Nakagawa et al (2004), que concluíram que, dentre os ambientes testados, a refrigerador e freezer mostram-se mais favoráveis à conservação de sementes aveia preta comparativamente ao ambiente de câmara seca. …”
Section: Tabela 3 Comprimento Da Parte Aérea (Cpa Cm) Comprimento unclassified
“…According to Toledo et al (2007), in the first stage of this study, storage of sudangrass seeds in frost free e freezer environments improves physiological quality. Similarly, Nakagawa et al (2004) found that maintaining seeds in frost free and freezer conditions can preserve physiological quality of black oat seeds compared to storage in dry chamber. However, it is possible those environment conditions become inappropriate to preserve quality as storage time progresses and deleterious effects of low temperature begin to take place.…”
Section: The Equation Adjusted To Mean Germinationmentioning
confidence: 93%